Evaluating organic bread wheat as a rotation crop for organic dairy farms. Issue 2 (20th February 2017) - Roche, Erin H.; Mallory, Ellen B.; Molloy, Thomas; Kersbergen, Richard J.
Abstract: The rising demand for local, organic bread wheat ( Triticum aestivum L.) in the northeastern USA may be an economic and agronomic opportunity for organic dairy producers. Bread wheat must produce adequate grain yields and crude protein (CP) levels to be profitable as a food crop and must complement the on-farm production of high-quality dairy feed. A field study evaluated bread wheat and perennial forage performance in five 3-year crop sequences all ending in a perennial legume/grass forage. The sequences differed by wheat type (winter or spring) and the crop prior to wheat: (1) corn silage ( Zea mays L.), (2) soybean ( Glycine max L.) or (3) one-year-old perennial forage. Wheat sequences were compared with a sequence of two years of corn silage followed by a new perennial forage seeding and with a continuous perennial forage control. Winter wheat spike density, wheat aboveground biomass and nitrogen uptake were always greater than spring wheat. Wheat grain yield and CP were strongly affected by wheat type, with winter wheat having greater yield but lower CP than spring wheat. At one site-year, winter wheat CP was 15 g kg −1 higher following perennial forage than following corn. Only spring wheat met the bread flour industry standard for CP. Newly established perennial forage following wheat had higher yields and legume composition in both years, along with higher projected milk yields in one year, than the continuous perennial forage. Three-year net revenue based on off-farm sales were on average US$ 741 ha −1 higher for sequences with winter wheat than those with spring wheat, and were equal to the perennial forage control. Rotations that included wheat would likely be more competitive if straw were sold or used on the farm, or, if topdressing practices or varietal choice were used to increase grain protein levels of winter wheat.